Falciform ligament abscess with disseminated intrahepatic foci: a case report - Tadao Kuribara; Itaru Shigeyoshi; Tatsuo Ichikawa; Kiyoshi Osa; Takeshi Inoue; Satoshi Ono; Kozo Asanuma; Shiori Kaneko; Takayuki Sano; Kouta Matsubara; Naoko Irie; Kanako Suzuki; et al. (Surgical Case Reports)
Abstract Background Falciform ligament abscess (FLA) is a rare disease, and its diagnosis can be challenging without typical image findings of an abscess. We report a patient with FLA that presented as a mass, with an indistinct border between it and the liver, in addition to disseminated foci within the liver. This made it difficult to determine whether it was FLA or a malignancy. Case presentation A 69-year-old man presented with epigastric pain. Contrast-enhanced computed tomography revealed a 25-mm mass below the middle of the diaphragm. Based on an initial diagnosis of infection of the falciform ligament, we administered conservative antibiotic treatment and there was initial improvement in the patient’s clinical condition and laboratory data. However, he continued to experience mild epigastric pain. A month later, imaging studies revealed enlargement of the falciform ligament mass and the emergence of a new nodule in the liver, whereas laboratory findings showed re-elevated C-reactive protein levels. Since conservative treatment had failed, we decided to perform surgery. Considering the imaging study findings, malignant disease could not be ruled out. Based on the operative findings, we performed combined resection of the falciform ligament, left liver, and gallbladder. Histopathological examination of the resected specimens revealed extensive neutrophil infiltration and the presence of giant cells and foam cells within the lesions. These findings were indicative of abscess. Pseudomonas aeruginosa was cultured from the pus in the falciform ligament mass and bile in the gallbladder. Although multiple abscesses postoperatively developed in the residual portion of the liver, they could be treated through antibiotic therapy. Conclusions FLA can spread to both adjacent and distant organs via its rich vascular and lymphatic networks. When FLA displays atypical image findings and/or an atypical clinical course, it can be difficult to distinguish it from malignant disease. In such cases, surgical treatment, with intraoperative pathological diagnosis, should be attempted.